Development of an Android Application for Monitoring the SMART Aquaponics System for Cultivating Catfish and Water Spinach Plants - Viving Frendiana; Morrin Nadya Pangesti (Jurnal Poli-Teknologi, 2025)
Aquaponics is a combination of aquaculture systems in the form of fish and hydroponic cultivation in the form of plants. Catfish growth will be optimal in water conditions with a temperature of 26°C - 30°C and a water pH of 6 - 9. Therefore, monitoring aquaponic water quality is needed to improve fish and plant growth. To facilitate the monitoring of water quality and plant growth, an Android-based mobile application "My Aquaponic" was created. This Android application uses the Firebase database platform. The data values displayed on the application are water temperature, water pH, water level, plant height, fish feeding status, and visual plant images. Quality testing of the My Aquaponic application is based on the ISO 25010 standard and other tests, namely data value accuracy. In testing the accuracy of data values, aspects of functional suitability, portability, and compatibility get a percentage of 100% in the 'Very Feasible' category. Testing the performance efficiency aspect obtained an average CPU performance of 3.914% and an average memory usage of 246.276 KB. Testing usability aspects with the System Usability Scale (SUS) method gets an average SUS value of 86.5 and based on the SUS Score percentile rank table falls into the adjective rating category 'Excellent' with grade "B" and acceptability range "Acceptable".